The level of antiretroviral therapy (ART) adherence among orphan children and adolescents living with HIV/AIDS: A systematic review and meta-analysis - Kamau, Stanley Githaiga; Akatusasira, Rita; Namatovu, Angella; Kibet, Emmanuel; Ssekitto, Joseph Mayanja; Mamun, Mohammed A.; Kaggwa, Mark Mohan (Plos one, 2024)
Background: Many children and adolescents living with HIV have ended up as orphans. Due to HIV taking away their parents leaves them deprived of their most important social network and support, which predisposes them to poor adherence to antiretroviral therapy (ART). Various studies have shown poor adherence to ART among orphaned children and adolescents. This systematic review and meta-analysis, therefore, aims to determine the level of ART adherence among orphaned children and adolescents living with HIV/AIDS. Methods: This PROSPERO registered review (CRD42022352867) included studies from PubMed, Google Scholar, Scopus, Web of Science, Africa Journal Online, and selected HIV/AIDS journals from data inception to June 01, 2022. We included articles published in all languages that report the prevalence of adherence to ART among children and adolescent orphans (single parent orphans and/or double orphans) living with HIV/AIDS. We excluded qualitative studies, case studies, opinion papers, and letters to editors. We used the random-effect model to calculate the pooled prevalence of ART adherence based on the highest prevalence provided by the various methods in a particular study. We used the Joanna Briggs Institute Appraisal tool for the prevalence study to evaluate for risk of bias in the included studies. The Egger’s test was used to assess small study effects. Results: Out of 1087 publications identified from the various databases, six met the selection criteria. The included six studies had a total 2013 orphans living with HIV/AIDS. The pooled prevalence of ART adherence was 78.0% (95% Confidence Interval: 67.4–87.7; I2 = 82.92%, p<0.001) and ranged between 7.6% and>95%, using one of the following methods: pill count, caregiver’s self-report, clinical attendance, and nevirapine plasma levels (above threeμg/mL). The factors associated with adherence were pill burden, caregiver involvement, stunting, and caregiver relationship. Limitation: There was a high level of heterogeneity in the finding. Conclusion: Approximately four fifth of orphan children and adolescents living with HIV/AIDS adhere to ART. Strategies to improve adherence among this group should be prioritized, especially among the double orphaned children and adolescents.
Keywords: Antiretroviral therapy; Orphans; HIV/AIDS; Adolescent children